Plantation Sector Policy Governance by the Regional Government of Riau Province (Leading Commodities Study) - Febrian, Ranggi Ade; Yuza, Ahmad Fitra (SCAD Independent, 2023)
This study tried to analyze the problems of the plantation sector in Riau Province from the point of view of governance policies carried out by the Riau Provincial government. Palm oil is still a leading commodity in Riau Province. This research problem focused on the governance of oil palm plantation policies in Riau Province as the first strategic issue. The added value of oil palm plantations had yet to improve the community's economy due to the slow downstream program. This study used the concept of governance, consisting of three dimensions: actor, structural, and empirical. Using qualitative research methods, this study concluded that the first dimension influences the policy governance of the oil palm plantation sector: actors were dominated by entrepreneurs, totaling 233 companies from an area of 1.569 million hectares. The two structural dimensions were dominated by six environmental studies on the management of oil palm plantation policies and the realization of the Riau Province APBD budget structure. The three empirical dimensions were dominated by land destruction and land conflicts for oil palm plantations, which impact the policies of the regional government of Riau Province.